Religious Materialism in Sachet Packaging Al-Qur'an Sales on The @Quranfi_ Account on Tiktok - Maula, Merdita Rizqia Nikma (Aqlam: Journal of Islam and Plurality, 2024)
Abstract: This study aims to examine the phenomenon of using the Qur'an in the form of sachet packaging which is often utilized for independent ruqyah, as part of the study of the Living Qur'an. This phenomenon reflects the adaptation and integration of sacred texts in the lives of modern people in order to obtain blessings, protection, or healing. This research uses a qualitative approach, involving social research steps to obtain descriptive data in the form of words and pictures. Data sources consist of primary data obtained from the comments of followers of the @Quranfi_ TikTok account and secondary data from related scientific works. Three questions that will be discussed First, how is the application of ruqyah in the use of sachet packaged Qur'anic verses. Second, how is the meaning of the word shifa as a medicine in the Qur'an. Third, how Tiktok social media users respond to the sale of Qur'anic verses on the @Quranfi_ account. As a result, TikTok as a popular social media, provides profitable business opportunities. The @Quranfi_ account utilizes TikTok to market the Qur'an in sachet form which has caused various reactions from netizens. Indonesian-speaking netizens generally see this sale as a form of commercialization of religion, causing debate. In contrast, English-speaking netizens gave positive reviews, pointing out the satisfaction and benefits of the product. This difference in response may be influenced by cultural differences.Keywords: Living Qur'an, Ruqyah, TiktokAbstrak: Penelitian ini bertujuan untuk mengkaji fenomena penggunaan al-Qur'an dalam bentuk kemasan sachet yang sering dimanfaatkan untuk ruqyah mandiri, sebagai bagian dari kajian Living Qur'an. Fenomena ini mencerminkan adaptasi dan integrasi teks suci dalam kehidupan masyarakat modern guna memperoleh berkah, perlindungan, atau penyembuhan. Penelitian ini menggunakan pendekatan kualitatif, melibatkan langkah-langkah penelitian sosial untuk memperoleh data deskriptif berupa kata-kata dan gambar. Sumber data terdiri dari data primer yang diperoleh dari komentar pengikut akun TikTok @Quranfi_ dan data sekunder dari karya ilmiah terkait. Tiga pertanyaaan yang akan menjadi pembahasan Pertama, bagaimana penerapan ruqyah dalam penggunaan ayat al-Qur’an kemasan sachet. Kedua, bagaimana pemaknaan kata syifa sebagai obat dalam al-Qur’an. Ketiga, bagaimana respon Pengguna media sosial Tiktok terhadap penjualan Ayat-ayat al-Qur'an di akun @Quranfi_. Hasilnya, TikTok sebagai media sosial yang populer, memberikan peluang bisnis yang menguntungkan. Akun @Quranfi_ memanfaatkan TikTok untuk memasarkan al-Qur’an dalam bentuk sachet yang menimbulkan berbagai reaksi dari netizen. Netizen berbahasa Indonesia umumnya melihat penjualan ini sebagai bentuk komersialisasi agama, menimbulkan perdebatan. Sebaliknya, netizen berbahasa Inggris memberikan ulasan positif, menunjukkan kepuasan dan manfaat dari produk tersebut. Perbedaan respon ini mungkin dipengaruhi oleh perbedaan budaya.Kata Kunci: Living Quran, Ruqyah, Tiktok